With Friends Like These…: Research Methods and the Marginalization of Philosophy - Boyles, Deron (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
This exploratory essay considers how and why humanities research is excluded, co-opted, or othered in methods courses and methods course offerings for education research at an R1 institution. While not generalizable (ironically?), concerns have also been raised by philosophers of education that philosophy is not taught or is rarely taught as a research method in colleges of education (Norris, 2021). As though there are only two kinds of research—quantitative and qualitative—this paper asks why humanities methods are rare in an R1 education research core. The short answer might point to numbers: there simply are not that many graduate students in history and philosophy of education. The longer answer, however, arguably involves scholarly turf wars waged within the politics of inquiry. This paper provides a brief overview of the history and politics of the methods wars, an explanation of a research core and the courses constituting it at Georgia State University, and a view from the outside looking in: peering over the qual and quant gate to see that philosophy is already there, but denied credibility, acknowledgement, and understanding.